Analysis Of Factors Influencing The Occupation Of Fraud Detection - Gen Norman Thomas; Lely Indriaty (Jurnal Akuntansi, 2023)
This study analyzes the influence of Forensic Accounting, Investigative Audit Capability and Auditor Experience on Fraud Detection in the Perspective of BPK and Central BPKP Auditors. The population of BPK and Central BPKP employees in Jakarta totaled 218 people, and the sample obtained was 97 people. The research method is quantitative to test the hypothesis and the data is processed by Smart PLS 3.00. The findings show that Forensic Accounting has no effect on fraud detection. Investigative Audit Ability has a significant effect on fraud detection and Auditor Experience has a significant effect on Fraud Detection. The results of the study show that forensic accountants are not fully involved in fraud detection efforts so that the influence of forensic accountants plays little role in fraud detection.